2017
DOI: 10.1371/journal.pone.0174559
|View full text |Cite
|
Sign up to set email alerts
|

Custom RT-qPCR-array for glaucoma filtering surgery prognosis

Abstract: Excessive subconjunctival scarring is the main reason of failure of glaucoma filtration surgery. We analyzed conjunctival and systemic gene expression patterns after non penetrating deep sclerectomy (NPDS). To find expression patterns related to surgical failure and their correlation with the clinical outcomes. This study consisted of two consecutive stages. The first was a prospective analysis of wound-healing gene expression profile of six patients after NPDS. Conjunctival samples and peripheral blood sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 50 publications
2
10
0
Order By: Relevance
“…IL-8 also increases proliferation and migration of endothelial cells as well as wound angiogenesis [33,34]. Our results, in the same line as those of others [6], show that overexpression of VEGF-A and IL-8 could be used as an indicator of conjunctival fibrosis following filtering surgery.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…IL-8 also increases proliferation and migration of endothelial cells as well as wound angiogenesis [33,34]. Our results, in the same line as those of others [6], show that overexpression of VEGF-A and IL-8 could be used as an indicator of conjunctival fibrosis following filtering surgery.…”
Section: Discussionsupporting
confidence: 90%
“…One year after surgery, however, only the expression of TGF-β1 and ITG-β3 was reduced. And, in peripheral blood, the most evident changes occurred also during the first 15 days after surgery, when 12 genes (IL-1β, CEBPD, HIF-1α, ITG-β2, TNFRSF1A and CASP1, among others) were induced [6]. These results suggested that conjunctival fibrosis developed after filtration surgery could have a significant genetic component driven by an altered expression of specific genes.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations